PERILAKU KERJA INOVATIF PEKERJA SEKTOR EVENT MANAGEMENT DI KOTA PEKANBARU - Kurniawan, Buyung; Sari, Komala; Suci, Afred (Jurnal Daya Saing, 2024)
This study addresses the scarcity of literature on innovative work behavior within the event management sector in Indonesia, particularly through the lens of the Job Demands-Resources (JD-R) model, while incorporating creative culture as an enriched dimension of job resources. The research examines the impact of job demands on innovative work behavior, with job satisfaction as a mediating variable and creative culture as a moderating factor. A cross-sectional survey involved 122 employees working in seminar, training, and certification event organizations in Pekanbaru. Data analysis using PROCESS Macro Model 1 and Model 4 reveals that high job demands negatively affected job satisfaction but, conversely, stimulated greater innovative behavior among workers. Job satisfaction partially mediated the relationship between job demands and innovative work behavior, while the moderating role of creative culture was not statistically significant